Diffuse vascular ectasia of the antrum, duodenum, and jejunum in a patient with nodular regenerative hyperplasia. Lack of response to portosystemic shunt or gastrectomy. Issue 4 (April 1993) - Calès, P; Voigt, J J; Payen, J L; Bloom, E; Berg, P; Vinel, J P; Pradère, B; Broussy, P; Pascal, J P
Abstract : The case is reported of a 70 year old man who presented with severe anaemia because of chronic gastrointestinal blood loss. This loss was ascribed to vascular ectasia resembling the gastric antral vascular ectasia syndrome but extended to include the antrum, the duodenum, the jejunum, and, possibly, the cardiac area. This condition was associated with portal hypertension as a result of nodular regenerative hyperplasia. Consecutive treatments including sucralfate, prostaglandin E2, propranolol, organic nitrates, pentoxyphilline, corticosteroids, endoscopic sclerotherapy, portosystemic shunt, total gastrectomy, proved ineffective.